Quantum Dots Affect Actin Cytoskeleton Reorganization, Resulting in Impaired HeLa and THLE-2 Cell Motility - Mileah Metcalf; Abhishu Chand; Kyoungtae Kim (Micro, 2025)
Quantum dots (QDs) are nanoparticles with intrinsic fluorescence. Recent studies have found that metal-based QDs often impart toxic effects on the biological systems they interact with. Their undefined limitations have offset their potential for biomedical application. Our study aimed to address the research gap regarding QDs’ impacts on the intracellular actin cytoskeleton and the associated structures. Our XTT viability assays revealed that QDs only reduced viability in transformed human liver epithelial (THLE-2) cells, whereas HeLa cells remained viable after QD treatment. We also used confocal microscopy to evaluate the morphological changes in THLE-2 induced by QDs. We further investigated cell protrusion morphology using phalloidin-Alexa488 which selectively labels F-actin. The fluorescent microscopy of this phalloidin label revealed that QD treatment resulted in the redistribution of actin filaments within both THLE-2 and HeLa cells. We also report that the average number of focal adhesions decreased in QD-treated cells. As actin filaments at the cell are peripherally linked to the extracellular matrix via talin and integrin and are thus a crucial component of cell motility, we conducted a migration assay. The migration assay revealed that cell motility was significantly reduced in both THLE-2 and HeLa cells following QD treatment. Our findings establish that the internalization of QDs reduces cell motility by rearranging actin filaments.